Phosphorus fertilization reduces the severity of charcoal rot (Macrophomina phaseolina) and the arbuscular mycorrhizal protection in soybean. Issue 6 (18th September 2018) - Spagnoletti, Federico N.; Leiva, Micaela; Chiocchio, Viviana; Lavado, Raul S.
Abstract: The effects of phosphorus (P) application on the relationship between the arbuscular mycorrhizal fungus (AMF) Rhizophagus intraradices and the pathogen Macrophomina phaseolina (charcoal rot) affecting soybean ( Glycine max L.) are unknown. We evaluated the effects of P on both the severity of the pathogen and the AMF protection against the charcoal rot in soybean. We conducted greenhouse experiments with a randomized multifactorial design with ten replications. The treatments were: two concentrations of P as superphosphate (0 and 50 kg of P ha −1 ), inoculated and non‐inoculated with the AMF R. intraradices, and infected and non‐infected with M. phaseolina . Soybean was seeded in pots containing 1 kg of sterilized substrate soil : sand : perlite (7 : 3 : 2). When soybean completed pod formation (R4 phenological stage), the plants were harvested. Plant parameters, mycorrhizal colonization, and disease severity were measured. The presence of M. phaseolina negatively affected soybean biomass, but AMF inoculation improved it. Phosphorus reduced AMF colonization but not arbuscules percentage. Moreover, both P and AMF inoculation had a negative effect on disease severity, although P also reduced mycorrhizal protection. These results suggest that phosphorus application could reduce disease severity, but can simultaneously partially reduce the AMF protection against the pathogen. These effects should be considered in agricultural integrated management practices of soybean.